Neuromonitoring with near-infrared spectroscopy (NIRS) in aneurysmal subarachnoid haemorrhage: a systematic review protocol. Issue 11 (10th November 2020) - Bensaidane, Mohamed Reda; Turgeon, Alexis F; Lauzier, François; English, Shane W; Leblanc, Guillaume; Francoeur, Charles L
Abstract : Introduction: Aneurysmal subarachnoid haemorrhage (aSAH) is a devastating disease associated with high mortality and morbidity. The main threat to patients is delayed cerebral ischaemia (DCI). Near-infrared spectroscopy (NIRS) is a recent technology allowing continuous, non-invasive cerebral oximetry that could permit timely detection of impending DCI and appropriate intervention to improve outcomes. However, the ability of regional oxygen saturation to detect DCI, its association to the outcome, or benefits of any interventions based on NIRS data, are lacking. Our aims are to evaluate NIRS technology both as a therapeutic tool to improve outcomes in aSAH patients and as a diagnostic tool for DCI. Methods and analysis: MEDLINE, EMBASE, Web of Science, the Cochrane Central Register of Controlled Trials and the Cochrane Database of Systematic Reviews will be searched from their inception and without language restriction. Our search strategy will cover the themes of subarachnoid haemorrhage and cerebral oximetry, without limitations regarding studied outcomes. We will identify all observational and interventional human studies of adult patients hospitalised after aSAH that were monitored using NIRS. Functional outcome measures, including the modified Rankin Scale, the Glasgow Outcome Scale and the Barthel Index, will constitute the primary outcome. The Cochrane Risk of Bias tool will be used for randomised controlled trials, the ROBINS-I tool to assess non-randomised studies of interventions and the Newcastle-Ottawa Scale for cohort or case–control studies. The Quality Assessment of Diagnostic Accuracy Studies-2 will be applied to studies evaluating NIRS diagnostic accuracy for DCI. We will evaluate the quality of the evidence of the effect based on the Grading of Recommendations Assessment, Development and Evaluation methodology. Ethics and dissemination: Dissemination will proceed through submission for journal publication, trial registry completion and abstract presentation. Ethics approval is not required. PROSPERO registration number: CRD42020077522.